2018
DOI: 10.1177/0963689718761658
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Brain-Derived Neurotrophic Factor on MicroRNA Expression Profile in Human Endothelial Progenitor Cells

Abstract: The mechanisms underlying proangiogenic function of brain-derived neurotrophic factor (BDNF) are not fully understood. The current study was designed to explore the microRNA (miRNA) profile in human early endothelial progenitor cells (EPCs, also referred to as CFU-Hill cells) treated with BDNF. Treatment of early EPCs with BDNF for 7 d significantly increased the colony formation of outgrowth endothelial cells. BDNF suppressed the expression of miR-4716-5p, miR-3928, miR-433, miR-1294, miR-1539, and miR-19b-1*… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 22 publications
0
10
0
Order By: Relevance
“…A decrease in miR-636 is also involved in the recovery from heart failure due to dilated cardiomyopathy (25). Furthermore, in human endothelial cell progenitors, brain-derived neurotrophic factor is able to increase miR-636 expression (34). Interestingly, miR-636 manifests other biological effects; for instance, circulating miR-636 is involved in the elimination of hepatitis C virus (HCV) and also in liver regeneration.…”
Section: Discussionmentioning
confidence: 99%
“…A decrease in miR-636 is also involved in the recovery from heart failure due to dilated cardiomyopathy (25). Furthermore, in human endothelial cell progenitors, brain-derived neurotrophic factor is able to increase miR-636 expression (34). Interestingly, miR-636 manifests other biological effects; for instance, circulating miR-636 is involved in the elimination of hepatitis C virus (HCV) and also in liver regeneration.…”
Section: Discussionmentioning
confidence: 99%
“…Considering this report and our results, a higher level of miRNA-4669 might contribute to the protection of vascular disease such as IS and arterial occlusive disease. Furthermore, a previous study reported the effect of BDNF on regenerative function of endothelial progenitor cells (EPCs), depending on the expression changes of miRNAs [27]. The treatment of BDNF could increase the expression of miRNA-4669 in EPCs [27].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, a previous study reported the effect of BDNF on regenerative function of endothelial progenitor cells (EPCs), depending on the expression changes of miRNAs [27]. The treatment of BDNF could increase the expression of miRNA-4669 in EPCs [27]. BDNF production was increased on the surface of blood vessels with damaged endothelium, exerting beneficial effects on regenerative function of EPCs [28].…”
Section: Discussionmentioning
confidence: 99%
“…MiR-1539 is 21 nucleotides long, to date, a few articles have been published ( 18 20 ). He et al observed that miR-1539 was inhibited by brain-derived neurotrophic factor, which stimulated angiogenesis and promoted endothelial cell survival ( 18 ).…”
Section: Introductionmentioning
confidence: 99%
“…MiR-1539 is 21 nucleotides long, to date, a few articles have been published ( 18 20 ). He et al observed that miR-1539 was inhibited by brain-derived neurotrophic factor, which stimulated angiogenesis and promoted endothelial cell survival ( 18 ). Ayaz et al indicated that miR-1539 overexpression was putatively involved in the pathological process of senile macular degeneration, with oxidative stress ( 19 ), whereas Veija et al reported that miR-1539 was associated with polyomavirus-positive Merkel cell carcinoma ( 20 ).…”
Section: Introductionmentioning
confidence: 99%